Pili and lipopolysaccharide of Pseudomonas aeruginosa bind to the glycolipid asialo GM1. - Gupta, S K (1994)
This study investigated which adhesins of Pseudomonas aeruginosa interact with the glycolipid asialo GM1, using solid-phase binding and thin-layer chromatography assays. Radioiodinated pili and flagella contaminated with lipopolysaccharide (LPS) bound to the glycolipid. When LPS was reduced to acceptable levels in pilus and flagellum samples, only pili specifically bound to the glycolipid. Commercial, radiolabeled LPS as well as whole bacteria of strain ATCC 19660 also bound to asialo GM1. Binding was specific, competitive, and saturable. Organ cultures of whole mouse eyes and scanning electron microscopy techniques were used also, and strain ATCC 19660 was inhibited from corneal binding by exogenous pili or commercial LPS and inhibition was concentration dependent for both. Binding of radiolabeled strain ATCC 19660 bacteria to neutral lipids extracted from bovine corneal epithelial tissue showed that the bacteria bound to a glycolipid which migrated at a position similar to that of an asialo GM1 standard and that the glycolipid stained positively with an antibody specific for asialo GM1. The data provide evidence that pili (reduced LPS) and LPS of P. aeruginosa bind to asialo GM1 glycolipid and that the glycolipid is not restricted to the mouse cornea.